Autoantibodies to type II collagen: occurrence in rheumatoid arthritis, other arthritides, autoimmune connective tissue diseases, and chronic inflammatory syndromes. Issue 4 (April 1988) - Choi, E K; Gatenby, P A; McGill, N W; Bateman, J F; Cole, W G; York, J R
Abstract : Serum IgG antibodies to native and denatured human type II collagen (Col II) were measured using an enzyme linked immunosorbent assay (ELISA). One hundred and thirty one patients with various forms of arthritis such as rheumatoid arthritis (RA), ankylosing spondylitis (AS), psoriatic arthritis (PSA). Reiter's Syndrome (RS), osteoarthritis (OA), and gout, 60 with autoimmune connective tissue disease, and 37 with the chronic inflammatory conditions--graft versus host disease and leprosy--were studied. With the exception of RS, PSA, OA, and gout, significant levels of Col II antibodies were detected in each disease group. Blocking studies with types I and II collagen on selected serum samples confirmed the specificity to native Col II, though some cross reactivity was apparent with denatured collagen. The patients with RA who were Col II antibody positive tended to fall into stage III of disease progression. There was, however, no correlation with rheumatoid factor, erythrocyte sedimentation rate, or disease duration and this, together with the finding that Col II antibodies are present in a wide array of diseases, makes their role in the pathogenesis of RA questionable. They may arise as a secondary disease perpetuating mechanism in some patients, or in turn may be an epiphenomenon secondary to generalised disturbed immunoregulation or B cell hyperreactivity, or both, that characterises these clinical conditions.